Effect of integrated vermicompost and chemical nitrogen fertilizer for productivity of bread wheat (Triticum aestivum L.) - Gemeda, Firaol; Chimdessa, Temesgen; Takale, Chalsissa; Desalegn, Mintesinot; Fikadu, Olifan; Tadesse, Amanuel; Regasa, Chaltu (Journal of Scientific Agriculture, 2024)
The study was conducted at Horo district on six (6) farmers’ fields to investigate the effect of integrated vermicompost and chemical nitrogen fertilizer for bread wheat and the soil nutrient content. The treatments consist of without any fertilizer, recommended chemical NP fertilizer, 100% N equivalent vermicompost + recommended P2O5, 75% N equivalent Vermicompost + 25% recommended N + recommended P2O5, 50% equivalent Vermicompost + 50% recommended N + recommended P2O5 and 25% equivalent Vermicompost + 75% recommended N + recommended P2O5. The experimental design was a randomized complete block design (RCBD) with three replications. Dendea seed variety with a rate of 150 Kg ha-1 was used for the trial. ANOVA analysis for after harvesting soil parameters showed significant (P<0.05) differences among treatments for available phosphorus, organic carbon, exchangeable acidity and cations exchange capacity while pH and exchangeable Ca and Mg were not statistically significant among the treatments. ANOVA showed that the treatments significantly influenced all collected yield and yield related parameters of the crop. Relatively the highest crop yield and yield related traits were obtained from T2 (recommended chemical fertilizer) while the lowest was from control (without fertilizer). The highest net income (91971.70 birr/ha) was obtained from 25% equivalence vermicompost + 75% recommended N + recommended P2O5. To have more confidence in the technology; it should be verified in the same area with the same management procedure.